Triangulation and the importance of establishing valid methods for food safety culture evaluation. (October 2017) - Jespersen, Lone; Wallace, Carol A.
Abstract: The research evaluates maturity of food safety culture in five multi-national food companies using method triangulation, specifically self-assessment scale, performance documents, and semi-structured interviews. Weaknesses associated with each individual method are known but there are few studies in food safety where a method triangulation approach is used for both data collection and data analysis. Significantly, this research shows that individual results taken in isolation can lead to wrong conclusions, resulting in potentially failing tactics and wasted investments. However, by applying method triangulation and reviewing results from a range of culture measurement tools it is possible to better direct investments and interventions. The findings add to the food safety culture paradigm beyond a single evaluation of food safety culture using generic culture surveys. Graphical abstract: Highlights: Establishes importance of triangulation for valid food safety culture evaluation Compares data from scale, performance documents, and semi-structured interviews Confirms need for multiple methods for trustworthy evaluation of food safety culture Applies culture coding framework to interview transcripts and performance documents Inter-coder and construct validity, and discrimination in food safety culture profiles